The relationship between distance to hospital and patient mortality in emergencies: an observational study. Issue 9 (21st August 2007) - Nicholl, Jon; West, James; Goodacre, Steve; Turner, Janette
Abstract : Objectives: Reconfiguration of emergency services could lead to patients with life-threatening conditions travelling longer distances to hospital. Concerns have been raised that this could increase the risk of death. We aimed to determine whether distance to hospital was associated with mortality in patients with life-threatening emergencies. Methods: We undertook an observational cohort study of 10 315 cases transported with a potentially life-threatening condition (excluding cardiac arrests) by four English ambulance services to associated acute hospitals, to determine whether distance to hospital was associated with mortality, after adjustment for age, sex, clinical category and illness severity. Results: Straight-line ambulance journey distances ranged from 0 to 58 km with a median of 5 km, and 644 patients died (6.2%). Increased distance was associated with increased risk of death (odds ratio 1.02 per kilometre; 95% CI 1.01 to 1.03; p<0.001). This association was not changed by adjustment for confounding by age, sex, clinical category or illness severity. Patients with respiratory emergencies showed the greatest association between distance and mortality. Conclusion: Increased journey distance to hospital appears to be associated with increased risk of mortality. Our data suggest that a 10-km increase in straight-line distance is associated with around a 1% absolute increase in mortality.